PENGARUH MUTU PELAYANAN TERHADAP KEPUASAN PASIEN BPJS RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH KOTA MATARAM TAHUN 2022 - I Made Putu Sudiartha Hartawan; Zaini, Zaini (Nusadaya Journal of Multidiciplinary Studies, 2022)
Health services will produce clinical outcomes, benefits obtained by patients, and patient experiences in the form of satisfaction or disappointment, the attitude and behavior of BPJS service providers shown by employees in providing services to the community politely, The level of patient satisfaction with services is an important factor that develops a service delivery system that is responsive to complaints customers, and waiting times and maximize the impact of services on patients. Study this is an analytic observational research with cross-sectional data design and conducted for identify through gift questionnaire, then analyze for look for there is whether or not connection quality service with level satisfaction patient participant BPJS Health in Installation Treat Mataram City Regional General Hospital Road. The sample of this study was 97 respondents who were outpatient BPJS patients at the Mataram City General Hospital. Based on the results of research on Service Quality with Patient Satisfaction who feel dissatisfied patient amount 5 people (5,2%), Meanwhile Very satisfied patient amount 32 people (33,0%), and Patient satisfied totaling 60 people (61.8% ), can be explained Probability value (p value) Spearman rho correlation test obtained value = 0.000 < 0.05, (Significant), the strength of the relationship = 0.776 (means Strong Positive), meaning the better the quality services will have a positive effect on BPJS Outpatient Patient Satisfaction at the Mataram City Regional General Hospital in 2022.